Enhancing Mathematical Representation and Reasoning Through Metacognitive Problem-Based Learning - Rahmat Hidayat; Rahmat Saleh (MASI Mandiri Edukasi, 2026)
Mathematical representation and reasoning are critical competencies that students often struggle to master. This study aims to evaluate the effectiveness of the Metacognitive Problem-Based Learning (MPBL) model in enhancing these abilities, while also examining the predictive roles of self-efficacy and metacognitive awareness. Using a quasi-experimental pretest-posttest non-equivalent control group design, a sample of 350 secondary students in Indonesia was selected via cluster random sampling. The experimental group (n=200) received MPBL, while the control group (n=150) followed conventional instruction. Results indicated that the MPBL group achieved significantly higher N-gains in mathematical representation (0.72,